2007
DOI: 10.1111/j.1872-034x.2007.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of chymase‐dependent angiotensin II formation in the progression of human liver fibrosis

Abstract: These results suggest that chymase-dependent angiotensin II formation may play an important role in hepatic fibrosis of patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…Fun et al (72) demonstrated the significance of chymase-dependent angiotensin II formation to the progression of tubulointerstitial fibrosis in obstructed kidneys in hamsters. In human liver fibrosis, both chymase and angiotensin II levels were significantly augmented, and significant correlations between chymase and angiotensin II levels, between chymase level and fibrotic degree, and between angiotensin II level and fibrotic degree were observed (73). Furthermore, chymase inhibition significantly attenuated the liver fibrosis in experimental animal models (74,75).…”
Section: Target Diseases Other Than Cardiovascular Diseasesmentioning
confidence: 74%
“…Fun et al (72) demonstrated the significance of chymase-dependent angiotensin II formation to the progression of tubulointerstitial fibrosis in obstructed kidneys in hamsters. In human liver fibrosis, both chymase and angiotensin II levels were significantly augmented, and significant correlations between chymase and angiotensin II levels, between chymase level and fibrotic degree, and between angiotensin II level and fibrotic degree were observed (73). Furthermore, chymase inhibition significantly attenuated the liver fibrosis in experimental animal models (74,75).…”
Section: Target Diseases Other Than Cardiovascular Diseasesmentioning
confidence: 74%
“…Other molecules mediate the interaction of Kupffer cells and Ito cells, as well as other cells involved in the liver fibrosis, to develop deposition of extracellular matrix. Vasodilator and vasoconstrictor substances such as nitric oxide, norepinephrine, angiotensin II, and endothelin are also involved in the mechanism of liver fibrosis (Hirose et al 2007;Kitamura and Hayashi 2008;Komeda et al 2008;Koshy et al 2005;Miller et al 2007;Moreno and Muriel 2006). IL-10 has been involved in the control of hepatic fibrosis due to Kupffer cell deactivation (Thompson et al 1998), and it was elevated in serum from patients with VL, decaying exponentially after therapy (de Medeiros et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…In human autopsy and biopsy cirrhotic livers, the expression of chymase is increased compared to that in normal livers, and it is suggested that the chymase contributes to the liver fibrosis [31] . Recently, it has been shown that, in human chronic cirrhosis, chymase-positive cells and activity are increased and Ang II formation is increased (but ACE activity is unaltered) compared to non-cirrhosis or early cirrhosis [32] . This suggests that chymase-dependent Ang II formation has a role in the fibrosis associated with liver cirrhosis [32] .…”
Section: Fibrosismentioning
confidence: 99%
“…Recently, it has been shown that, in human chronic cirrhosis, chymase-positive cells and activity are increased and Ang II formation is increased (but ACE activity is unaltered) compared to non-cirrhosis or early cirrhosis [32] . This suggests that chymase-dependent Ang II formation has a role in the fibrosis associated with liver cirrhosis [32] .…”
Section: Fibrosismentioning
confidence: 99%